Cutaneous Larva Migrans - Mohamad Mimbar Topik; Rizky Adinda Nurhidayah Marpaung (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Introduction: Cutaneous larva migrans (CLM) is a parasitic infestation that commonly occurs in warm climates among people who have contact with contaminated soil. This is caused by the migration of hookworm larvae into human skin. Clinically, itchy, erythematous, linear serpiginous tracts appear within days to months after exposure to infected sand or soil. Diagnosis is based on clinical presentation. CLM can heal on its own and usually resolves within a few weeks to several months without treatment . Case report: This case report is about a 30-year-old female patient with complaints of itching on the little finger of the left foot since 4 days ago accompanied by multiple erythematous papules with serpiginous arrangement, the surface of the left dorsal leg. Conclusion: CLM associated with hookworm is diagnosed clinically based on the typical clinical appearance, as well as a history of travel to endemic areas and exposure to contaminated soil/sand.